Clinical and Biochemical Manifestations of Severe Sickle Cell Anemia in Adult Patients in Steady State in Ile-Ife, Nigeria - Oguntoye Oluwatosin Oluwagbenga; Ndububa Dennis A.; Yusuf Musah.; Bolarinwa Rahman A.; Ayoola Oluwagbemiga O. (Sudan Journal of Medical Sciences)
Background: There are documented established markers (indices) of disease severity in patients with sickle cell anemia (SCA) and they determine the course of the disease. This study investigated the pattern and prevalence of some of these markers of disease severity in adult patients with SCA in steady state attending the hematology clinic of a federal tertiary teaching hospital in Ile-Ife, Nigeria.